2017
DOI: 10.5137/1019-5149.jtn.19342-16.0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of scalp markers and three-dimensional sliced computer tomography reconstructions of the skull transverse-sigmoid sinus groove in the retrosigmoid approach

Abstract: The 3D sliced CT reconstruction of the skull transverse sinus and sigmoid sinus groove was helpful in the approach of retrosigmoid craniotomy for sinus exposure, sinus protection, and the prevention of cerebrospinal fluid leakage and pseudomeningocele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Te asterion is defned as the intersection of the occipitomastoid, parietomastoid, and lambdoid sutures [15]. While it has been widely considered to overlie the superior curvature of the sigmoid sinus, more recent studies have noted signifcant anatomical variations in this positional relationship [2,[9][10][11]. Te spatial relationship between the asterion and the superior curvature of the sigmoid sinus is not constant from one individual to another and cannot be relied on to locate the keyhole for a retrosigmoid craniotomy accurately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te asterion is defned as the intersection of the occipitomastoid, parietomastoid, and lambdoid sutures [15]. While it has been widely considered to overlie the superior curvature of the sigmoid sinus, more recent studies have noted signifcant anatomical variations in this positional relationship [2,[9][10][11]. Te spatial relationship between the asterion and the superior curvature of the sigmoid sinus is not constant from one individual to another and cannot be relied on to locate the keyhole for a retrosigmoid craniotomy accurately.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bozbuga et al [7] and da Silva et al [8] present key studies (anatomical, radiological, and clinical) reporting that the asterion is not a reliable landmark for burr hole placement in the retrosigmoid approach. Indeed, an increasing number of studies have demonstrated that there is considerable anatomic variation in the relationship between the asterion and the transverse-sigmoid junction, and incorrect venous sinus localization may result in sinus injury or insufcient surgical exposure [2,[9][10][11]. While other skull-surface landmarks are also used to locate the transverse-sigmoid junction, they have anatomic variations, and some are too far from the surgical incision to be practical for surgical use [12].…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical structures asterion, inion, superior nuchal line and suprameatal triangle were used as landmarks to locate the junction between transverse and sigmoid sinuses (15,16). However, further studies revealed that there were inconsistencies with the transverse and sigmoid junction and the location of these anatomical structures (15,17). Also, asterion was difficult to locate intra-operatively (19).…”
Section: Discussionmentioning
confidence: 99%
“…Asterion, inion, superior nuchal line and suprameatal triangle were such structures believed to be helpful in locating the transverse sigmoid sinus junction (15,16). However, during recent years cadaveric research on the location of these was found to be inconstant among individuals (15,17).…”
Section: Introductionmentioning
confidence: 99%
“…Teranishi (2014) 18 88 pacientes 6.5 mm inferior, 6.5 mm lateral al asterion. Wang et al (2018) 21 108 pacientes Localización individualizada utilizando TC 3D y marcadores en cuero cabelludo. Zhou et al (2019) 22 16 hemisferios y 20 pacientes Localización de punto prequirúrgico basado en cálculos preoperatorios y referencias anatómicas.…”
Section: Pacientesunclassified